2019
DOI: 10.1177/1745499919828908
|View full text |Cite
|
Sign up to set email alerts
|

Multilingualism and multiliteracy in primary education in India: A discussion of some methodological challenges of an interdisciplinary research project

Abstract: In the Indian context, concerns have been raised for many years about the learning outcomes of primary school children (see Banerji, Bhattacharjea and Wadhwa, 2013). The complexity of the issue makes it difficult to advise stakeholders on what needs to be done to improve learning in primary schools in India. As Alcott and Rose (2017) have shown that low socioeconomic status (SES) is one of the key factors which negatively affect learning outcomes, the focus of the Multilila project ('Multilingualism and Multil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
1
10
0
1
Order By: Relevance
“…In this study, Hindi-speaking mothers showed a disinclination towards translated Hindi leaflets. India is one of the most multilingual countries in the world, where a large number of regional dialects are spoken, including Punjabi, Tamil, and Telegu [ 38 ]. It is thought this could have contributed to the participants expressing difficulty in comprehending the Hindi leaflets.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Hindi-speaking mothers showed a disinclination towards translated Hindi leaflets. India is one of the most multilingual countries in the world, where a large number of regional dialects are spoken, including Punjabi, Tamil, and Telegu [ 38 ]. It is thought this could have contributed to the participants expressing difficulty in comprehending the Hindi leaflets.…”
Section: Discussionmentioning
confidence: 99%
“…The Multilingualism and Multiliteracy (MultiLila) project 1 (Tsimpli et al 2019(Tsimpli et al , 2020 aims to increase awareness and knowledge about both languages of instruction, learning levels and cognitive abilities of the multilingual children in India. The project is a four-year longitudinal study, beginning in 2016, and operates across three research sites: Delhi, Hyderabad (in Telangana state) and Patna (in Bihar).…”
Section: The Context Of the Current Studymentioning
confidence: 99%
“…The data was collected from a total of 27 government schools across two sites -New Delhi, India's capital, and in Hyderabadthe capital of the state of Telangana in southern India. The children were from underprivileged backgrounds and from low-SES families residing in urban slum and non-slum areas and were attending government schools with relatively low funding and resources (Tsimpli et al 2019(Tsimpli et al , 2020). 2 Hindi is the majority language in Delhi and Telugu in Hyderabad.…”
Section: Samplementioning
confidence: 99%
“…Children of low SES usually tend to enroll in government schools which have very little funding; these children also do not receive enough parental support at home. Their exposure to print is almost absent-or restricted only to marketplaces (Tsimpli et al 2019). Therefore, there is an urgent need to understand the factors affecting learning outcomes in children coming from disadvantaged backgrounds.…”
Section: The Indian Contextmentioning
confidence: 99%